Exploring the Possibility of Using Distance Learning for Nurses - Saeid Ebrahimi; Yousef Mehdipour; Jahanpour Alipour; Marziyeh Bostani (مجله انفورماتیک سلامت و زیست پزشکی, 2016)
Introduction: In order to achieve educational goals in developing countries like Iran, it is essential to use new training methods especially distance learning.  The aim of this study was to investigate the possibility of using distance learning for nurses in teaching hospitals affiliated with Zahedan University of Medical Sciences.